Immunologic landscape of human hepatic hemangiomas and epithelioid hemangioendotheliomas - Thomann, Stefan; Metzler, Thomas; Tóth, Marcell; Schirmacher, Peter; Mogler, Carolin (Hepatology communications, 2024)
Background: - The missing requirement for resection for the majority of hepatic hemangiomas (HH) and tissue scarcity for rare diseases such as hepatic epithelioid hemangioendotheliomas (HEHE) complicate the characterization of the spatial immunovascular niche of these benign and malignant vascular neoplastic diseases. - Methods: - Two tissue cohorts containing 98 HHs and 13 HEHEs were used to study entity-specific and disease stage-specific endothelial cell (EC) phenotype and immune cell abundance. Using semiquantitative assessment, annotation-based cell classifiers, digital cell detection on whole slides, and tissue microarrays, we quantified 23 immunologic and vascular niche-associated markers and correlated this with clinicopathologic data. - Results: - Both HH and HEHE ECs were characterized by a CD31high, CD34high, FVIII-related antigenhigh expression phenotype with entity-specific expression differences of sinusoidal EC markers Stabilin1, Stabilin2, CD32, and Lymphatic Vessel Endothelial Hyaluronan Receptor 1 (LYVE-1). Cell detection identified an HH margin-prevailing immunologic response dominated by Myeloperoxidase+ (MPO+) macrophages, CD3+ and CD8+ T cell subsets, and B cells (CD20+, CD79A+). In HEHE, increased CD68+ and CD20+ cell demarcation of lesion margins was observed, while CD3+ and CD8+ T cells were equally detectable both marginally and intralesionally. Stage-specific pairwise correlation analysis of HH and HEHE revealed disease entity-specific immunologic infiltration patterns as seen by high CD117+ cell numbers in HH, while HEHE samples showed increased CD3+ T cell infiltration. - Conclusions: - ECs in HH and HEHE share a continuous EC expression phenotype, while the expression of sinusoidal EC markers is more highly retained in HEHE. These phenotypic differences are associated with a unique and disease-specific immunovascular landscape.